Sustained Competitive Advantage: Temporal Dynamics and the Incidence and Persistence of Superior Economic Performance - Wiggins, Robert R.; Ruefli, Timothy W. (Organization Science, 2002)
Competitive advantage is a key concept in strategic management research for a number of reasons—not the least of which is that an avowed consequence of its attainment is held to be superior economic performance. However, few prior empirical studies have directly and systematically documented the incidence or prevalence of persistent superior economic performance. The research reported here is based on empirical studies of a large number of industry samples for which longitudinal data were stratified by levels of performance using a new methodology and then analyzed in terms of their dynamics. This new stratification technique was used in lieu of autoregressive methods employed in prior studies of performance persistence to allow for a true outlier analysis because persistent superior economic performance both has been argued theoretically, and found empirically, to be rare. Detailed results from a sample of 6,772 firms in 40 industries over 25 years are presented to illustrate the findings that: (1) while some firms do exhibit superior economic performance, (2) only a very small minority do so, and (3) the phenomenon very rarely persists for long time frames. These results, while not providing direct support for a particular extant strategic management or economic theory concerning firm performance, are most consonant with the resource-based view of the firm and have implications for significant aspects of other received strategic management and economic theories.